Sulfomethylation reactivity enhanced the Fenton oxidation pretreatment of bamboo residues for enzymatic digestibility and ethanol production - Liu, Zhaoming; Zhang, Min; Hou, Qinpei; Shi, Zhengjun; Yang, Haiyan; Wang, Dawei; Yang, Jing (Frontiers in Bioengineering and Biotechnology, 2024)
Bamboo residues was first subjected to sulfomethylation reaction at 95 °C for 3 h, followed by Fenton oxidation pretreatment at 22°C for 24 h.The synergistic effect of combined pretreatment dramatically improved enzymatic digestibility efficiency, with maximum yield of glucose and ethanol content of 71.11% and 16.47g/L, respectively, increased by 4.7 and 6.11 time comparing with the single Fenton oxidation pretreatment. It was found that the hydrophobicity of substrate, content of surface lignin, degree of polymerization, and specific surface area have significant effects on the increase of enzymatic saccharification efficiency. It also revealed that sulfomethylation pre-extraction can improve the hydrophilicity of lignin, leading to the lignin dissolution, which was beneficial for subsequent Fenton pretreatment of bamboo biomass. This work provides some reference for Fenton oxidation pretreatment of bamboo biomass, which can not only promote the utilization of bamboo in southwest China, but also enhances the Fenton reaction in the bamboo biorefinery.